2010
DOI: 10.5012/bkcs.2010.31.9.2488
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Polonium Nuclides in a Water Sample with Solvent Extraction Method

Abstract: A method is described for the determination of the Po nuclides in a water sample. After the Po nuclides were purified from interfering elements in a water sample using a manganese dioxide precipitation followed by a solvent extraction method, the Po nuclides were deposited onto the silver plate. A large volume of the water sample was effectively pretreated with manganese dioxide precipitation method. To determine the optimum conditions for plating Po, the effects of the pH, volume, temperature and time on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…Liquid-liquid extraction methods were used for separating Po from Pb and Bi. This technique uses several types of organic extracting such as isopropyl ether, diisopropyl ketone, methyl isobutyl ketone, tributyl phosphate, methyl isobutyl ketone, diethylammonium diethyl dithiocarbamate, diethylam-monium diethyldithiocarbamate, thenoyltrifluoroacetone, tri-n-octylphosphine oxide (Jia., 2004;Jia., 2008;Kim., 2009;Lee., 2010). The limitation of this method is that the process is complicated and requires many extraction steps and during the separation process, many mixed radioactive wastes were generated (Thakur et al, 2020).…”
Section: * Liquid-liquid Extraction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liquid-liquid extraction methods were used for separating Po from Pb and Bi. This technique uses several types of organic extracting such as isopropyl ether, diisopropyl ketone, methyl isobutyl ketone, tributyl phosphate, methyl isobutyl ketone, diethylammonium diethyl dithiocarbamate, diethylam-monium diethyldithiocarbamate, thenoyltrifluoroacetone, tri-n-octylphosphine oxide (Jia., 2004;Jia., 2008;Kim., 2009;Lee., 2010). The limitation of this method is that the process is complicated and requires many extraction steps and during the separation process, many mixed radioactive wastes were generated (Thakur et al, 2020).…”
Section: * Liquid-liquid Extraction Methodsmentioning
confidence: 99%
“…During this step, usually add a small amount of ascorbic acid, hydroxylamine hydrochloride, and sodium citrate to limit the influence of Fe 3+ , Ca 2+ , Mg 2+ ions; to effect of polonium deposition and to get high spectrum resolution (Figgins., 1961;Smith., 1984;IAEA., 2009). There were affecting factors of the efficiency, including pH, temperature, sample volume, and time (Guérin., 2015;Lee., 2010;Porntepkasemsan., 2011;Bagnall., 1990;Thakur. et al, 2020).…”
Section: Source Preparationmentioning
confidence: 99%
“…These include diethylammonium diethyl dithiocarbamate (DDTC), diethyl dithiocarbamate (DDC), Tri-isoctylamine (TIOA), and tricytle phosphine oxide (TOPO) in toluene (Matheny, 2011). Several studies Lee et al (2010), Martin and Hancock (1992) and Kim, Lee, and Martin (2009) have reported use of diethylammonium diethyl dithiocarbamate (DDTC) in CH 3 CCl 3 for the extraction of Po from aqueous solution in recent studies. Solvent extraction study on the hydrolysis of tracer concentration of polonium (IV) in nitrate solutions (Hataye, Suganuma, & Sakata, 1981), a-hydroxyisobutyric acid solutions (Johansson, Malmbeck, Wierczinski, & Skarnemark, 2001) and tri-n-butyl Phosphate (Chen, 2013) have been also reported.…”
Section: Solvent Extractionmentioning
confidence: 98%
“…The Sr-Spec resin is used for isolation of polonium isotopes from environmental samples (ELAfiffi & Borai, 2006). The extractant is a crown ether (1 M bis-4,4 0 (5 0 0-tbutyl-cyclohexano-18,6-crown ether) dissolved in 1-octanol) (Lee, Lee, Song, Kim, & Martin, 2010). The structure of the extractant is shown in Fig.…”
Section: Ion Exchangementioning
confidence: 99%
“…The method of determination of 210 Po in environmental samples, especially in water samples has to be optimized as there have been reported difficulties for the same [15,16]. Various radiochemical procedures for 210 Po were described in a method review article [17].…”
Section: Introductionmentioning
confidence: 99%